Sonochemical oxidation of arsenite in aqueous phase - Cui, M.; Lee, S.; Jang, Min; Kweon, B.; Jo, H.; Khim, J. (IOP Publishing, 2011)
The objective of this research is to assess critically the experimental rate data for sonochemical oxidation of arsenite [As(III)] at different frequencies and powers in the aqueous phase. The oxidative conversion of As(III) into arsenate [As(V)] was >90% in the range of 283 to 450 kHz. With a power density of 69WL-1, the oxidation of As(III) for 40min at 283kHz showed a second-order rate constant of 7:1 × 102 M-1 s-1, whereas it was 3:8 × 103M-1 s -1 at 450 kHz. As calculated by the calorimetric method, the power transferred into samples was in the range of 7-34.5 W with the two frequencies of 283 or 450 kHz. Approximately 100% oxidation efficiency was obtained with a frequency of 450 kHz and 34.5 W. As the pretreatment process, oxidation by sonication has potential applications to groundwater contaminated with both As(III) and As(V). © 2011 The Japan Society of Applied Physics.